Asean's Role in The Settlement of International Disputes on China's Aggressation Against Taiwan - Ega Permatadani; Ida Ayu Rosida; Rifda Ayu Akmaliya; Sonia Amelia; Anang Dony Irawan (Indonesian Journal of Law and Policy Studies, 2022)
ASEAN is a country located in the Asia Pacific region. ASEAN itself is declared in Bangkok and has 10 Member States. ASEAN's location is very strategic as a way of trade and industry in the ASIA region. If there is a conflict that occurs in the ASIA Region, the ASEAN countries will also be affected by the conflict. Like the conflict that is happening in East Asia, namely the conflict between China and Taiwan. China itself is a major power country on the continent of Asia. Because as a major power country, it must have a strong territory and trade, China itself uses its existence to cooperate in good international trade. However, Taiwan, whose position is as a territory of mainland China, has even declared its independence, even thoughTaiwan is an integral part of China. This sparked anger from China, and became acivil conflict. China itself carried out its aggression against its own brother, namely Taiwan. Military aggression carried out by China against Taiwan has violated war crimes in accordance with the core provisions of international crimes, namely the Rome Statute. The violations that occurred are in Articles 5 and 8 of the 1998 Rome Statute. China has been intimidating and depriving Taiwanese civilians of their human rights. Where here China is the main perpetrator of war crime violations. Actions taken by China have become an important focus for other ASEAN countries, where the importance of ASEAN's role in resolving this dispute is based on the TAC and United Nation mechanism.